Integration of Islamic Education And Science In Realizing A Superior Generation For Indonesia Gold 2045 in Pesantren Tebuireng - Sa'adiyah, Maidatus; Azah, Nur; Kumala, Akhsinatul; Arini, Aida; Rosyidin, Muhammad Abror; Raharjo, Resdianto Permata (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2024)
Pesantren is known as a traditional educational institution with the yellow book. However, with all its traditionalism, pesantren have been in contact with the development of science. Thus, pesantren emerged that integrated their traditional Islamic education with science and technology, such as Pesantren Sains Tebuireng Jombok and Pondok Putri Pesantren Tebuireng Kesamben Jombang. Then, this can be linked to the role of pesantren in helping to realize the vision of Indonesia Gold 2045, welcoming 100 years of Indonesia. This research aims to document, describe, and understand how these two institutions integrate Islamic education and science to create an excellent generation toward the Golden Indonesia 2045. In addition, it is also to provide inspiration for other pesantren institutions, that the intersection of science with pesantren is not a taboo. The research approach is descriptive qualitative with an observational research method. Active and full participatory observation (total participant observation) was chosen with the aim of having the researcher as the main instrument or tool of the research, directly and fully involved in every process and activity related to the research subject.